2020
DOI: 10.1042/bst20190386
|View full text |Cite
|
Sign up to set email alerts
|

Keeping in touch with the membrane; protein- and lipid-mediated confinement of caveolae to the cell surface

Abstract: Caveolae are small Ω-shaped invaginations of the plasma membrane that play important roles in mechanosensing, lipid homeostasis and signaling. Their typical morphology is characterized by a membrane funnel connecting a spherical bulb to the membrane. Membrane funnels (commonly known as necks and pores) are frequently observed as transient states during fusion and fission of membrane vesicles in cells. However, caveolae display atypical dynamics where the membrane funnel can be stabilized over an extended perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Of note, caveola formation or stability is assisted by other proteins implicated in cancer, such as PACSINs [106,146] and EHDs [84,110]. A detailed discussion of these proteins and their participation in related processes is however beyond the scope of this review and can be found elsewhere [58,66,91,131,149].…”
Section: Role Of Cav1 In Migrationmentioning
confidence: 99%
“…Of note, caveola formation or stability is assisted by other proteins implicated in cancer, such as PACSINs [106,146] and EHDs [84,110]. A detailed discussion of these proteins and their participation in related processes is however beyond the scope of this review and can be found elsewhere [58,66,91,131,149].…”
Section: Role Of Cav1 In Migrationmentioning
confidence: 99%
“…As a structural component of caveolae, caveolin-1 exerts crucial function in a variety of cellular functions, consisting of cell growth, adhesion, signal transduction, migration, senescence, development, and tumorigenesis (Boscher and Nabi, 2012;Ketteler and Klein, 2018;Volonte and Galbiati, 2020). Caveolin-1 also played an important role in mechanosensing that reflects the response the mechanical forces (extracellular matrix stiffness, vascular shear stress, and muscle stretching) reaching on the plasma membrane and affects the membrane integrity and repair (Dewulf et al, 2019;Del Pozo et al, 2020;Hubert et al, 2020;Liu, 2020;Singh and Lamaze, 2020). Caveolin 1 involves in the EMT in lung cancer (Garnett, 2016;Shi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…GSN (Silacci et al, 2004) regulates the formation of the actin skeleton by assembling or dissembling actin filaments and forming molecular complexes that rapidly dissociate and reform to accomplish actin remodeling. PACSIN2 is a membrane sculpting protein (Hubert et al, 2020) known to play an important and unique role in megakaryocyte membrane invagination (Begonja et al, 2015;Chitu and Stanley, 2015) and impact platelet formation and function. CELF2 (Barreau et al, 2006) and MBNL1 (Meola et al, 2013) are RNA-binding proteins, with recognized roles in mRNA splicing; and their epigenetic loss associated with aberrant growth inhibition and poor clinical outcome in other cancers (Pique et al, 2019).…”
Section: Increasing Alternative Splicing Of Genes That Are Also Differentially Expressed Confirm Increasingly Impaired Proteostasis By Mpmentioning
confidence: 99%